2017
DOI: 10.1021/acs.analchem.6b04960
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Highly Azide-Reactive and Thermosensitive Biofunctional Reagent for Efficient Enrichment and Large-Scale Identification of O-GlcNAc Proteins by Mass Spectrometry

Abstract: O-linked β-N-acetylglucosamine (O-GlcNAc) is a ubiquitous post-translational modification of proteins in eukaryotic cells. Despite their low abundance, O-GlcNAc-modified proteins play many important roles in regulating gene expression, signal transduction, and cell cycle. Aberrant O-GlcNAc proteins are correlated with many major human diseases, such as Alzheimer's disease, diabetes, and cancer. Because of the extremely low stoichiometry of O-GlcNAc proteins, enrichment is required before mass spectrometry anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…The top 20 significantly enriched functional groups are listed in Figure E. Go annotation analysis of the enriched proteins indicated that O-GlcNAc modified proteins are implicated in a large scale of cellular pathways and molecular functions, as reported in the previous proteomic analysis. …”
Section: Resultssupporting
confidence: 55%
“…The top 20 significantly enriched functional groups are listed in Figure E. Go annotation analysis of the enriched proteins indicated that O-GlcNAc modified proteins are implicated in a large scale of cellular pathways and molecular functions, as reported in the previous proteomic analysis. …”
Section: Resultssupporting
confidence: 55%
“…Besides biotin–alkyne linkers, triarylphosphine derivatives, which readily react with azide-labeled molecules via Staudinger ligation, represent another alternative for O-GlcNAc enrichment. , Huo et al synthesized a triphenylphosphine-functionalized trimethylpiperidine (TFT) reagent consisting of three parts: a “click” group (toward azide-tagged peptides), a linker, and an affinity group mimicking TMT (which can reversibly bind to an anti-TMT antibody) (Figure C) . With this approach, the TFT-tagged O-GlcNAc peptides were enriched by using the anti-TMT antibody-conjugated agarose beads with a moderately high affinity ( K d = 86 pM) and then recovered by competitive elution under mild conditions.…”
Section: Large-scale Characterization Of O-glcnac Proteinsmentioning
confidence: 99%
“…The entries are organized by number of carbon atoms of the phosphane (and then grouped by publication), and it will cover examples up to beginning of 2020 (for not or only partly covered examples, see refs ).…”
Section: Mechanism and Stereochemistrymentioning
confidence: 99%